Photolysis of a mixture of anthracene and benzo[a]pyrene at ultra-trace levels in natural water with disinfection purposes (2020)
The photodegradation of anthracene (AN) and benzo[a]pyrene (BaP), two priority polycyclic aromatic hydrocarbons (PAHs), was examined at ultra-trace levels in surface water to elucidate their behaviour under several irradiance values and types of radiation. The emitting flux and the spectrum of the lamps were found to develop a crucial role in AN and BaP degradation since removal efficiencies of the target contaminants higher than 99% were found after 15 min of irradiation under an ultraviolet C (UVC) irradiance of 0.63 mW/cm2, corresponding to a fluence of 560.25 mJ/cm2. On the other hand, although ultraviolet A (UVA) lamps exhibited a higher irradiance compared to that of UVC lamps, they were not efficient for degrading the target PAHs. The removal kinetic studies corroborated these findings, being the AN elimination rate in surface water higher than that in deionized water at optimal operating conditions. Disinfection potential was also measured. A rapid microbial load inactivation, in terms of total coliforms naturally contained in the water matrix studied, was evidenced within 15 min of treatment for the fluence referred. However, after 24 hr in the dark, a regrowth was observed. Additionally, photolysis products more toxic than the parent compounds were found, which were not removed even by extending the treatment time. In this regard, it can be concluded that the individual action of UVC light for removing AN and BaP with disinfection purposes is not an efficient treatment; therefore, the use of radiation in combination with other kinds of treatments is required.